Fine particulate matter estimated by mathematical model and hospitalizations for pneumonia and asthma in children - César, Ana Cristina Gobbo; Nascimento, Luiz Fernando Costa; Mantovani, Katia Cristina Cota; Vieira, Luciana Cristina Pompeo (Sociedade de Pediatria de São Paulo, 2016)
AbstractObjective: To estimate the association between exposure to fine particulate matter with an aerodynamic diameter <2.5 microns (PM2.5) and hospitalizations for pneumonia and asthma in children.Methods: An ecological study of time series was performed, with daily indicators of hospitalization for pneumonia and asthma in children up to 10 years of age, living in Taubaté (SP) and estimated concentrations of PM2.5, between August 2011 and July 2012. A generalized additive model of Poisson regression was used to estimate the relative risk, with lag zero up to five days after exposure; the single pollutant model was adjusted by the apparent temperature, as defined from the temperature and relative air humidity, seasonality and weekday.Results: The values of the relative risks for hospitalization for pneumonia and asthma were significant for lag 0 (RR=1.051, 95%CI; 1.016 to 1.088); lag 2 (RR=1.066, 95%CI: 1.023 to 1.113); lag 3 (RR=1.053, 95%CI: 1.015 to 1.092); lag 4 (RR=1.043, 95%CI: 1.004 to 1.088) and lag 5 (RR=1.061, 95%CI: 1.018 to 1.106). The increase of 5mcg/m3 in PM2.5 contributes to increase the relative risk for hospitalization from 20.3 to 38.4 percentage points; however, the reduction of 5µg/m3 in PM2.5 concentration results in 38 fewer hospital admissions.Conclusions: Exposure to PM2.5 was associated with hospitalizations for pneumonia and asthma in children younger than 10 years of age, showing the role of fine particulate matter in child health and providing subsidies for the implementation of preventive measures to decrease these outcomes.

ResumoObjetivo: Estimar a associação entre exposição ao material particulado fino com diâmetro aerodinâmico inferior a 2,5 micra (PM2.5) e as internações por pneumonia e asma em crianças.Métodos: Estudo ecológico de séries temporais com indicadores diários de internação por pneumonia e asma, em crianças com até 10 anos, residentes em Taubaté (SP), e concentrações estimadas de PM2.5, entre agosto de 2011 e julho de 2012. Modelo aditivo generalizado de regressão de Poisson foi usado para estimar o risco relativo, com defasagem de zero até cinco dias após a exposição; o modelo unipoluente foi ajustado pela temperatura aparente, medida definida a partir da temperatura e umidade relativa do ar, sazonalidade e dia da semana.Resultados: Os valores dos riscos relativos para internações por pneumonia e asma foram significativos para lag 0 (RR=1,051; IC95% 1,016-1,088); lag 2 (RR=1,066; IC95% 1,023-1,113); lag 3 (RR=1,053; IC95% 1,015-1,092); lag 4 (RR=1,043; IC95% 1,004-1,088) e no lag 5 (RR=1,061; IC95% 1,018-1,106). O incremento de 5mcg/m3 de PM2.5 contribui para aumento no risco relativo para internações entre 20,3 a 38,4 pontos percentuais; no entanto, a diminuição de 5µg/m3 na concentração do PM2.5 resulta em menos 38 internações.Conclusões: A exposição ao PM2.5 esteve associada às internações por pneumonia e asma em crianças menores de 10 anos, mostrou o papel do material particulado fino na saúde da criança e forneceu subsídios para implantação de medidas preventivas para diminuírem esses desfechos.
Material particulado fino estimado por modelo matemático e internações por pneumonia e asma em crianças
Keywords: Asthma; Pneumonia; Air pollutants; Particulate matter; Child health; Mathematical models; Asma; Pneumonia; Poluentes do ar; Material particulado; Saúde da criança; Modelos matemáticos